Emerging adults and adulthood - Demoura, Ashley (Nova Science Publishers, 2021)
"This book comprises three chapters that each approach the subject of emerging adults from a different perspective. Chapter One examines the impact that parental involvement has on the personal development of emerging adults in China, with a specific focus on mental health, romantic involvement, and peer relationships. Chapter Two discusses the challenges faced by East Asian American girls and emerging adults and the protective factors that help mediate the core challenges this population faces. Lastly, Chapter Three provides a comprehensive literature review from a cross-cultural comparative perspective of the complicated pathways emerging adults face today and identifies key protective buffers and predictors that promote mental health, self-competence and identify achievements that lead to a more successful emergence into early adulthood"--